Post-Colonial Education Policies and Cultural Integration: A Comparison of Indonesia and Turkey - Yentür, Derya Berrak (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This study comparatively examines how education systems in Indonesia and Turkey are shaped in a post-colonial context and how they manage cultural diversity. Both countries have historically different colonial experiences and are home to large and diverse ethnic groups. The article analyzes the impact of post-colonial theory on the sociology of education and evaluates the role of educational policies on social integration and equal educational opportunity. Using qualitative and quantitative research methods, this study examines the historical development of education systems, cultural diversity management and regional differences in both countries in depth. The findings reveal the similarities and differences between the education policies of Turkey and Indonesia and provide policy recommendations for reducing inequalities in education and strengthening social integration. Moreover, this study provides an important comparative analysis to understand similar challenges and opportunities facing education systems in a global context. Examining how the education policies of Turkey and Indonesia have been reshaped in different ways by their postcolonial legacies and the implications of these processes for managing cultural diversity in education provides valuable insights for global education policy. In particular, the article provides an in-depth perspective on how the principles of justice and equity in education can be implemented and offers concrete recommendations for policymakers, educators and researchers. In this context, it also provides guidance for other multicultural societies seeking to reform their education systems.